Environmental characteristics shape macroinvertebrate community structure across spatiotemporal scales in a subtropical African river system - Linton F. Munyai; Busisiwe P. Gumede; Farai Dondofema; Tatenda Dalu (Scientific Reports)
Abstract Understanding the impact of human activities and environmental drivers on macroinvertebrate communities is critical to adequately manage river ecosystems under multiple stressors. In this study, we assessed macroinvertebrate community structure in relation to water and sediment chemistry. Samples (i.e., water, sediment and macroinvertebrates) were collected from 16 sites along the subtropical Luvuvhu River (South Africa) mainstem and its tributaries across two seasons (i.e., cool–dry (June), hot–wet (November)). The analysed data was assessed using multivariate analyses and diversity matrices. Significant differences were observed across seasons and river sections for most water (i.e., pH, temperature, resistivity, ammonium, phosphates) and sediment (i.e., potassium, sodium, copper, zinc, boron, sediment organic carbon) variables. Macroinvertebrates exhibited high diversity during hot–wet season compared to the cool–dry season, with a six distinct macroinvertebrates families (i.e., Odonata, Diptera, Coleoptera, Hemiptera, Trichoptera, Ephemeroptera) having a high taxon abundances. Based on CCA analysis, seasons were positively associated with CCA axis 2, and were characterised by high Mg, Na, pH, sediment organic carbon, ammonium and phosphates, with all highlighted variables having a significant effect on macroinvertebrate community composition. The results obtained from this study highlighted that water and sediment chemistry had significant associations with changes in macroinvertebrate communities and composition. Therefore, understanding the relationship between water and sediment chemistry, and macroinvertebrates diversity matrices in rivers that are impacted by human activities is essential for comprehending the integrity of river ecosystem and for providing guidance to conservation managers. This knowledge will assist on how to effectively manage and safeguard these systems against further deterioration from anthropogenic activities.